Hubungan Pemakaian Alat Kontrasepsi Dalam Rahim dengan Kejadian Kehamilan Ektopik - Ayu, Rosalina Pradana; Darto; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background:Ectopic pregnancy is a problem in gynecologic area that causes high maternal morbidity and mortality. Use of intrauterine device (IUD) is a hypothetic risk factor forectopic pregnancy. Progesterone content in the IUD can increase tubal implantation. Changes in theendometrium condition, leukocyte infiltration in the uterus, andÂ  accumulation of macrophages induced by IUD can cause extrauterine pregnancy when ovulation occurs. This study aimed to determine the relationship between IUD use and the risk for ectopic pregnancy, controlling for the effect of age. Methods:This study was analytic observational using case-control design. Thirty patients with ectopic pregnancy sampled by fixed disease sampling were compared with 60 patients with normal pregnancy at the Dr. Moewardi Hospital Surakarta. The data were collected from the medical records, then were analyzed for the relationship using multiple logistic regression model on SPSS 17 for Windows. Results:Women who used IUD had 9.33 times higher risk of ectopic pregnancy than women who did not use IUD (OR= 9.33; CI95%= 1.01 to 86.36; p = 0.049). The analysis has controlled for age as a confounding factor. Conclusion:There is relationship between IUD use and the risk for ectopic pregnancy, after controlling for age. Keywords:Intra-uterine device (IUD), ectopic pregnancy.